# Obtain all the zeroes of the polynomial X^4 - 3√2 x³ + 3x² +3 √2x - 4 = 0 , if two of it's zeroes are √2 and 2√2 ... Guys , Solve out !!!

1
by Galaxy
Let me try.....
is x in root here 3 √2x
it is not possible to solve bcoz it can't be solved here
but if u say i can solve it on paper and upload the file
Yeah I have also solved one question the same way and uploaded.You can do so

2015-10-01T21:29:00+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
P(x) =  x⁴ - 3 √2  x³ + 3 x² + 3√2  x - 4

given that (x - √2) , (x - 2√2) are factors of P(x) as √2 and 2√2 are two zeroes of P(x) = 0.

(x -√2) (x - 2√2) =  x²  -3√2 x + 4  is a factor of P(x).  let A be a constant.  We can write the constant term in the second factor by :  -4/4 = -1... dividing the constant terms.

let  (x² - 3√2 x + 4) (x² + A x -1 )  =  P(x)

Now compare the coefficients of x³ :  A - 3√2 = -3√2    =>  A = 0
coefficient of  x :  4A + 3√2 = 3√2        => A = 0

so  the other factors  are :  x² - 1 = 0
so  x = 1  and -1 are the other factors.

This method of multiplying the factors and comparing coefficients is simple.
click on thanks button above pls;;; select best answer
You're answer is always best !
There is a simple method. I overlooked....
sum of all four roots of P(x) is the - of coefficient of x cube. so it is 3√2. The sum of given two roots is 3 √2. So sum of two more roots is 0.
Now product of four roots is the constant term = -4... product of two given roots is 4. so product of two more roots is -4/4 = -1.....
Hence the polynomial is simple : x² - (0) x + (-1)
roots of this are +1 and -1.